French Adaptation of the Narcissistic Personality Inventory in a Belgian French-Speaking Sample - Braun, Stéphanie; Kempenaers, Chantal; Linkowski, Paul; Loas, Gwenolé (Frontiers in Psychology, 2016)
The Narcissistic Personality Inventory (NPI) is the most widely used self-report scale to assess the construct of narcissism, especially in its grandiosity expression. Over the years, several factor models have been proposed in order to improve the understanding of the multidimensional aspect of this construct. The available data are heterogeneous, suggesting one to at least seven factors. In this study, we propose a French adaptation of the NPI submitted to a sample of Belgian French-speaking students (n=942). We performed a principal component analysis on a tetrachoric correlation matrix to explore its factor structure. Unlike previous studies, our study shows that a first factor explains the largest part of the variance. Internal consistency is excellent and we reproduced the sex differences reported when using the original scale. Correlations with social desirability are taken into account in the interpretation of our results. Altogether, the results of this study support a unidimensional structure for the NPI using the total score as a self-report measure of the Narcissistic Personality Disorder in its grandiose form. Future studies including confirmatory factor analysis and gender invariance measurement are also discussed.